Construction et circulation des savoirs musicaux - Angélica Rigaudière (Revue d'anthropologie des connaissances)
Breitkopf & Härtel largely contributed to the development of a learned discourse on music. Based on an analysis of four journals founded by this music publisher, this article aims to examine how circulation of knowledge and scientific specialization during the 19th century were linked to the establishment of a publishing market. As part of a commercial strategy, the Allgemeine musikalische Zeitung (1798-1848; 1863-1882) intended to adress a general readership. The Jahrbücher für musikalische Wissenschaft (1863, 1867) defended the need to conciliate the accurate knowledge of the specialist and the broader outlook of the dilettante. The Zeitschrift der Internationalen Musikgesellschaft (1899-1914) and the Sammelbände der Internationalen Musikgesellschaft (1899-1914) are conceived to interest musicians and musicologists respectively.